Geotechnical Properties and Slopes Stability for Banks Soils in North Part of Shatt Al-Hilla at Meandering Sites, Babylon Governorate / Central of Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background:The northern regions of the Babylon Governorate, located on the Hilla River, suffering  from problems as the collapse and erosion of its banks, as well as the increase in sedimentation in the river, which reduces the River flow efficiency; due to the effect of the velocity river flow, which works on eroding one side of the river and sedimentation on the other side, forming meanders in the river.Materials and Methods:After the reconnaissance visit to determine the meandering sites. A detailed study of the area was carried out by drilling (6) test boreholes representing three areas( Al-Sadda, Al-Mahaweel ,and Sinjar),  two wells on both sides of the meander and at a depth of (10 m), for each borehole to observe the effect of the river flow velocity on the stability of slopes and to know the variation in soil properties, its bearing capacity and the consolidation on both sides of the river, and thus its effect on the engineering construction .Soil samples have been taken  to  carry out physical tests including: (moisture content test , specific gravity test , Atterberg limits tests , sieve analysis and hydrometer tests) ,also carried out engineering tests including: (permeability test , unconfined  & triaxial compressive strength test , direct shear test , consolidation test and bearing capacity) , soil chemical tests have been perform also which are (pH , total soluble salt , sulfate test , chloride test , gypsum test and organic matter test) .A study was also conducted for the stability of the banks slopes for the three stations, where the cross-section was monitored by the M9 device, as well as the height of the banks from both sides by the (LEVEL) device, Using the Geo-Studio 2021 program with soil properties and by using (Bishop), method the safety factor was extracted for the three stations For erosion-prone areas.Conclusion: The highest result of the safety factor was in Sinjar Station (2.5), then the banks of Al-Sadda Station, with a value of (2.3), and the lowest value of Al-Mahaweel Station, which amounted to (1.4). Under natural conditions, the average river flow level reaches it in year is (28.7 m) above sea level.Where all the stations were (safe), unless the water level increased or decreased. Also, the research reached a determination of the allowable bearing capacity  The soil of the banks reaches it before the landslide.